Ansiedade Social na Infância e Pré-Adolescência: Adaptação para o Português de Portugal da SASC-R - Martins, A.C (2014)
The Social Anxiety Scale for Children (revised form) - SASC-R evaluates the experience of social anxiety and avoidance felt by children and pre-adolescents in the context of relationship with their peers. This study aims to validate the Portuguese version of the SASC-R by confirmatory factor analysis using the structure proposed by the authors of the original scale. In a survey donewith 486 children between the ages of nine and 15 years, the results show that the scale reproduces the original factors, has a good internal consistency and a quite satisfactory construct validity. This study suggests that the SASC-R is a useful scale on the evaluation of social anxiety among children.